Willingness to pay for solid waste management services and associated factors in Mbarara District, Southwestern Uganda - Erastus Tugume; Abraham Muhwezi; Tom Murungi; Julius Kyomya; Edgar Mulogo Mugema; Richard Migisha; Moses Ntaro (PLOS Global Public Health, 2026)
Willingness to pay (WTP) for solid waste management services is essential for sustainability, yet it remains unassessed in Mbarara District. This study assessed the prevalence of WTP for solid waste management services and the associated factors among households in Mbarara District, Southwestern Uganda.This was a quantitative cross-sectional survey conducted among 250 individuals in households of Bwizibwera-Rutooma and Rubindi-Ruhumba town councils, Mbarara district. We used multistage sampling to select the administrative units and consecutively selected the participants from households. Data were collected using a 26-item interviewer-administered questionnaire, entered in Microsoft Excel and transferred to STATA version 17.0 for cleaning and analysis. Continuous variables were summarized using means and standard deviations, while categorical variables were pre sented as frequencies and proportions. Bivariate and multivariable logistic regression analysis at a 95% level of confidence was done to identify factors associated with WTP for solid waste management services.Overall, 62% (156/250; 95% C.I.: 56.2%- 68.2%) of the participants were willing to pay for solid waste management services. The majority, 64.1% (100/156), were willing to pay one thousand Uganda shillings or more for SWM. Factors associated with WTP for solid waste management services were; being male (aOR = 2.4, 95% CI: 1.2-4.6; p-value=0.011), having a monthly income>28 USD (aOR = 2.2, 95% CI: 1.7-4.1; p-value=0.015), disposing wastes using town council services (aOR = 7.75, 95% CI: 1.35-44.47; p-value=0.022) and receiving weekly waste collection services (aOR = 2.62; 95% CI: 1.06-6.50; p=0.038). The WTP for solid waste management services was relatively high and positively associated with being male, having a monthly income of>100,000 UGX, reliance on town council collection services, and weekly waste collection. Policymakers and local authorities should prioritize affordable, reliable waste collection and inclusive measures, like subsidies and targeted community engagement to boost participation and sustain waste management.
Keywords: Willingness to pay; Waste management; Uganda